Implementation of Genetic Algorithm in Making a Covid-19 Vaccination Schedule - K. Dilpani Laksmi; Bayu Angga Wijaya; Desniari Gea (Jurnal Mantik, 2021)
At the end of 2019, the World was attacked by a very deadly virus. Starting from the city of Wuhan in China, this virus began to grow and attack the world and became a pandemic. Until now the world is still being attacked by this pandemic. Various experts in this world took turns looking for a solution to this problem. Various studies and studies were carried out to find a way out and treatment. In the middle of 2020, research began to be intensively carried out to make a covid 19 vaccine. In doing things that are quite complicated, of course we need the help of technology to do it. In this case, we can use an algorithm in scheduling the covid 19 vaccination. In this regard, this study would like to discuss the application of genetic algorithms in making the covid 19 vaccination schedule. The genetic Algorithm was chosen because it can use many variables in its application compared to the FIFO method. The FIFO method is indeed simpler, the first to register will be scheduled, but to support more variables it is more efficient to use Genetic Algorithms. The use of genetic algorithms in this study was to find solutions and apply them to the program to schedule the covid 19 vaccination. genetics in scheduling accurate and effective COVID-19 vaccinations.